Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Mean value theorem

  1. Mar 30, 2006 #1
    Use the Mean Value Theorem to prove the inequality
    [tex]|\sin a - \sin b| \leq |a - b|[/tex] for all a and b.

    I know by the Mean Value Theorem, I can say:
    [tex]\sin a - \sin b = \cos c(a - b)[/tex]

    I've been trying to figure it out for awhile, but could not, so I peeked at my solution's manual. They assumed b < a, and said
    [tex]|\sin a - \sin b| \leq |\cos c||b - a| \leq |a - b|[/tex]

    how did they arrive at this?
    Last edited: Mar 30, 2006
  2. jcsd
  3. Mar 30, 2006 #2


    User Avatar
    Science Advisor
    Homework Helper

    What can you say about the bounds of [itex]|\cos c|[/itex]?
  4. Mar 30, 2006 #3


    User Avatar
    Science Advisor

    Are you aware that [itex]-1\le cos(x)\le 1[/itex]?
  5. Mar 30, 2006 #4
    Yes, but wouldn't that make it:
    [tex]|\sin a - \sin b| \geq |\cos c||b - a|[/tex] ?
    [tex]|\cos c||b - a| \leq |a - b|[/tex]

    And doesn't
    [tex]|b - a| = |a - b|[/tex] ?
  6. Mar 30, 2006 #5
    I think you're getting mixed up. Maybe it will help if you write your equation as:

    [tex]|\sin a - \sin b| = |\cos c||a - b|[/tex]
  7. Mar 31, 2006 #6
    If two numbers are equal then their absolute values are certainly also equal. So

    [tex]\sin \left( a \right) - \sin \left( b \right) = \cos \left( c \right)\left( {a - b} \right)[/tex]

    \Rightarrow \left| {\sin \left( a \right) - \sin \left( b \right)} \right| = \left| {\cos \left( c \right)} \right|\left| {a - b} \right|
    [/tex] (1)

    I would say that assuming a < b or vice versa is just to allow you to use the MVT. It makes no difference whether a or b is greater since you are dealing with absolute values. After all, |a| = |-a|.

    Anyway once you get to equation (1), all you need has been given to you. If you combine HallsofIvy and Galileo's hints then you should be able to draw the required conclusion.

    If you still can't see what they are suggesting then consider the following

    2 = 2.
    2 < 2(2) = 4
    2 < 3(2) = 6.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook